2022
DOI: 10.1037/pap0000385
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown dreams: Dream content and emotions during the COVID-19 pandemic in an italian sample.

Abstract: Beginning in March 2020, the Italian population was subjected to a lockdown lasting approximately 3 months due to the Coronavirus disease (COVID-19) emergency. Drawing on a quantitative and qualitative analysis of dream data, the present study aimed at exploring the effects of social isolation and the lockdown on Italian people's dreams, focusing on content and dominating emotions. An online survey was administered to 598 participants who aged 18-70 years (M = 30.9, SD = 10.9). In the survey, participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 121 publications
10
39
0
1
Order By: Relevance
“…However, most pandemic dream research has utilized cross‐sectional designs with dream changes quantified using Likert scale items. More detailed content or thematic analysis of recent dream reports has been used in some studies (Barrett, 2020 ; Giovanardi et al, 2021 ; Gorgoni et al, 2021 ); however, they have not asked participants to describe, in their own words, changes to their dream experiences. Therefore, more rich, in‐depth qualitative analysis is required to comprehensively define changes in dreaming during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…However, most pandemic dream research has utilized cross‐sectional designs with dream changes quantified using Likert scale items. More detailed content or thematic analysis of recent dream reports has been used in some studies (Barrett, 2020 ; Giovanardi et al, 2021 ; Gorgoni et al, 2021 ); however, they have not asked participants to describe, in their own words, changes to their dream experiences. Therefore, more rich, in‐depth qualitative analysis is required to comprehensively define changes in dreaming during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…According to other authors, however, the contents and emotions of dreams seem to be related to the difficulties imposed by the new reality of the pandemic [ 32 , 33 , 96 , 97 ]. In this context, some studies have shown that women respond more intensively to stressful events, tending also to incubate these events more into dreams [ 73 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, although not explicitly related to the social context, these themes related to the affective experiences of inefficacy, i.e., feeling blocked and unable to continue, helpless, and under threat. The challenge relating to the mastery of a coping device (e.g., blocked roads, a weapon) may have also represented the participants’ global psychological concerns, i.e., the diminished life opportunities and life plans put on hold during lockdowns with which students were struggling during this period [ 12 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In medical language and the media, illness is often described using military metaphors [ 53 ]. Likewise, COVID-19 was depicted as a “deadly enemy”, with doctors and health professionals being described as “heroes” or “soldiers” “fighting on the front line” in a “battle” against the pandemic and its lethal effects [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation